2017
DOI: 10.7759/cureus.1702
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis Induced by Nivolumab: A Case Report

Abstract: Nivolumab is a programmed cell death receptor (PD-1) inhibitor therapy for aggressive cancers; however, it poses a risk of immune-related adverse side effects. We present a 73-year-old male with renal cell carcinoma who developed myasthenia gravis (MG) after being treated with nivolumab, proven by acetylcholine receptor antibodies. Our patient presented with symptoms of fatigue and upper and lower extremity weakness, eventually resulting in respiratory failure as a result of MG. Nivolumab is an emerging therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We obtained data for 17 cases of ICI therapy followed by MG with hyperCKemia or anti‐striational antibody, as shown in Table . The patients in 15 cases had hyperCKemia and the patients in four of these cases complained of myalgia.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained data for 17 cases of ICI therapy followed by MG with hyperCKemia or anti‐striational antibody, as shown in Table . The patients in 15 cases had hyperCKemia and the patients in four of these cases complained of myalgia.…”
Section: Resultsmentioning
confidence: 99%
“…A high number of patients showed signs of cardiac involvement in the form of either elevated myocardial enzymes [11][12][13]21,22,26,32,39,46,50,60,71,72 , ECG changes 26,32,46 , abnormal echocardiography 71 , cardiac arrest 14 , or cardiac symptoms prior to death 30,41,48,71 . The coexistence of myasthenia, myopathy and myocarditis was also noted by Suzuki et al 73 .…”
Section: Nmj/myasthenia Gravis Myopathy and Neuropathy (Primary Research Question)mentioning
confidence: 99%
“…In a Japanese population, the incidence of myasthenia gravis was 0.12% in patients treated with nivolumab 9 . Of note, other authors found evidence of concurrent myositis and/or neuropathy, which indicates that side effects following nivolumab and pembrolizumab also involve neuromuscular tissue distal and proximal from the neuromuscular junction [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation